Cell‐Free Protein Synthesis: A Cell‐Free Platform Based on Nisin Biosynthesis for Discovering Novel Lanthipeptides and Guiding their Overproduction In Vivo (Adv. Sci. 17/2020). Issue 17 (9th September 2020) - Liu, Ran; Zhang, Yuchen; Zhai, Guoqing; Fu, Shuai; Xia, Yao; Hu, Ben; Cai, Xuan; Zhang, Yan; Li, Yan; Deng, Zixin; Liu, Tiangang
Abstract : In article number 2001616, Tiangang Liu and co‐workers develop a cell‐free protein synthesis (CFPS) platform that enables rapid discovery of novel lanthipeptides and guides lanthipeptide overproduction in vivo. This study extends the use of cell‐free systems to address the issue facing lanthipeptide research, while providing the possibility for developing CFPS platforms for other ribosomally synthesized and post‐translationally modified peptides studies.